Nurses' knowledge about integrative and complementary health practices (Research, Society and Development, 2020)
Objective: To identify nurses' knowledge about Integrative and Complementary Health Practices. Methodology: Field research, descriptive, quantitative, carried out online through the Google Forms Platform, with 508 nurses. The questionnaire was open for 34 days between the months of September and October 2019. Results: Participants of the study were nurses from 19 Brazilian states, most of them female, working in hospitals, followed by primary care, with a higher prevalence from 31 to 40 years of age, from one to five years of training and experience. Most are familiar with PICS and the policy of these therapies, the best known of which are acupuncture, homeopathy and music therapy. The most available in health services are acupuncture, reike and yoga. Most believe that PICS can be implemented in health services. However, these professionals do not wish to work in the area of PICS. Conclusion: It is essential that nurses carry out training related to PICS in order to expand their knowledge about therapies that promote health and improve the quality of life of individuals.